Gaza, tell us your stories - Omar, Haslina (Asia Pacific Institute of Advanced Research, 2016)
This paper takes a pscho-literary approach in discussing a collection of lightly fictionalized short stories by a group of new young Palestinian women creative writers and how they convey through personal accounts of lived experiences in their homeland that truth and hope cannot be silenced by injustice and oppression. It also seeks to throw some light into recent questions raised by American researchers in the area of personality psychology as to whether the narrative identity present in stories narrated by people in other societies and cultures are similar to those narrated by Americans who draw on their own life narratives to make sense of their lives and to cope with life’s challenges (McAdams & Guo, 2015). This paper discusses the collective narrative identity of emerging women writers living in the Gaza Strip whose creative resistance to injustice make up most of the 23 short stories in the anthology Gaza Writes Back (2014). As politically-oriented news dominate much of what the world listens to, much of the complex layers of war torn societies are brushed over and unfamiliar to the outside world. In discussing the very own narrative written in the English Language of a people who have been geographically and politically isolated and who have witnessed and been subjected to horrific violence in the form of military brutality for years, this paper seeks to generate further discussions and interest in their stories and hinder attempts to silence them.